Enhancing Parenting to Prevent Negative Discipline in Yogyakarta: Mixed Methods Study - Nafisah, Khilda Durrotun; Astuti, Andari Wuri; Rokhmah, Islamiyatur; Warsiti, Warsiti; Kit, Ayano (Jurnal Berita Ilmu Keperawatan, 2025)
Data show that 60% of children aged 2 to 14 have experienced physical punishment from their parents. Based on data from the Simfoni PPA KemenPPPA (Online Information System for the Protection of Women and Children), in 2023, there were 29,884 cases of violence recorded throughout Indonesia. Objective: This study aimed to enhance the parenting skills of prospective parents in the Bantul region to prevent the use of negative disciplinary methods on children. This study employed a mixed-methods design with a Sequential Explanatory approach. The quantitative phase used a pre-experimental design with a one-group pretest-posttest design, involving 37 prospective parents as the sample. The qualitative phase utilised Participatory Action Research, recruiting a sample of 5 couples of prospective parents, 2 counsellors, and 1 policy maker. The average attitude score of prospective parents before the intervention was 62.11, which increased to 80.38 after the intervention. A significant p-value of 0.000 < 0.05 indicates the rejection of the null hypothesis. This implies that the intervention concerning negative disciplinary measures on children has a significant impact on the attitudes of prospective parents. Conclusion: Several challenges faced by prospective parents in enhancing parenting skills include a lack of experience in child-rearing, mental unpreparedness for parenthood, and limited time due to work and other activities. The government needs to formulate policies that encourage positive parenting approaches and non-violent discipline, and launch awareness campaigns to educate the public about the dangers of negative disciplinary measures and the importance of positive parenting methods.